2020
DOI: 10.1111/jsap.13124
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of the utility of cross‐matching prior to first transfusion in cats: 101 cases

Abstract: Objectives: To: (1) assess the frequency of crossmatch incompatibility in naïve feline blood transfusion recipients using two crossmatching methods, (2) measure the effect of crossmatch incompatibility on change in packed cell volume following transfusion, (3) assess the frequency of acute transfusion reactions and errors in blood transfusions in cats and (4) assess the impact of crossmatch incompatibility on the likelihood of transfusion reactions. Materials and MethOds:Cats being administered a first AB-matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 18 publications
4
33
0
Order By: Relevance
“…Previous reports have already documented crossmatch incompatibilities and transfusion reactions in AB‐matched transfusion naïve cats, highlighting the presence of NOAb outside of the AB system 15‐22 . Our study supports the presence of non‐AB NOAb with 3.9% chance of detecting incompatibilities by randomly crossmatching 2 cats, which resulted in at least 7% of 258 type A cats having NOAb.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Previous reports have already documented crossmatch incompatibilities and transfusion reactions in AB‐matched transfusion naïve cats, highlighting the presence of NOAb outside of the AB system 15‐22 . Our study supports the presence of non‐AB NOAb with 3.9% chance of detecting incompatibilities by randomly crossmatching 2 cats, which resulted in at least 7% of 258 type A cats having NOAb.…”
Section: Discussionsupporting
confidence: 85%
“…Previous reports have already documented crossmatch incompatibilities and transfusion reactions in AB-matched transfusion naïve cats, highlighting the presence of NOAb outside of the AB system. [15][16][17][18][19][20][21][22] Our study supports the presence of non-AB NOAb with 3.9% chance of detecting incompatibilities by randomly crossmatching test and commercial gel-tube assay. 1 We chose to use the saline gel column technique because this method has been proven to be highly accurate in human medicine with a sensitivity between 97.58% and 100% and a specificity close to 100%.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Investigation of a larger number of IMHA cases is needed before concluding that small aggregates of erythrocytes are not evidence of agglutination, but our results suggest that until such studies becomes available, weak positive SATs should be confirmed by DAT. This should not be extrapolated to interpretation of pretransfusion slide-based crossmatches,27,28 as in this setting,…”
mentioning
confidence: 99%